2010
DOI: 10.1111/j.1365-2141.2010.08228.x
|View full text |Cite|
|
Sign up to set email alerts
|

Ten‐year follow‐up after intense chemoimmunotherapy with Rituximab‐HyperCVAD alternating with Rituximab‐high dose methotrexate/cytarabine (R‐MA) and without stem cell transplantation in patients with untreated aggressive mantle cell lymphoma

Abstract: SummaryMantle cell lymphoma (MCL) has a poor overall survival after treatment with conventional chemotherapy. Intense chemoimmunotherapy without consolidation stem cell transplantation is a potential therapeutic option. We report on a prospective Phase II study with rituximab in combination with fractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone (R‐Hyper‐CVAD) alternating with rituximab in combination with high‐dose methotrexate‐cytarabine (R‐MA) in untreated patients with diffuse and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
135
2
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 223 publications
(149 citation statements)
references
References 33 publications
7
135
2
5
Order By: Relevance
“…Similar efficiency has been shown for an even more intensified regime [10]; however, only the minority of patients was able to complete the full course in a multicenter setting [11].…”
Section: Introductionmentioning
confidence: 76%
“…Similar efficiency has been shown for an even more intensified regime [10]; however, only the minority of patients was able to complete the full course in a multicenter setting [11].…”
Section: Introductionmentioning
confidence: 76%
“…Although tolerating patients treated with the hyper-CVAD regimen had excellent response and survival rates of greater than 90% at 3 years and 4.6 years of time to treatment failure (TTF at 8yr , 16% if age>65, 46% if age<65) following 10 year observation period 7,38,57,58 , patients treated with conventional therapies have also reported to have similar 3 year survival rates 59,60 . The hyper-CVAD regimen without stem cell transplantation was not associated with a plateau in the survival curves (Figure 4) 57 . In this study, beta-2-microglobulin levels and IPI/MIPI scores were found to predict survival 57 .…”
Section: Role Of Chemotherapymentioning
confidence: 99%
“…The hyper-CVAD regimen without stem cell transplantation was not associated with a plateau in the survival curves (Figure 4) 57 . In this study, beta-2-microglobulin levels and IPI/MIPI scores were found to predict survival 57 . Hyper-CVAD regimen data may suggest high efficacy of the high-dose Ara-C (HIDAC) regimen, which needs to be tested in further clinical trials.…”
Section: Role Of Chemotherapymentioning
confidence: 99%
“…However, a plateau had not been observed and the median OS had not been reached at the time of publication. 11 Outcomes for patients 465 were compromised by treatment-related toxicities. The Nordic study group treated patients with a dose-intensified CHOP-like regimen (maxi-CHOP) alternating with R-high-dose cytarabine and followed by consolidation high-dose chemotherapy and auto-SCT.…”
Section: Introductionmentioning
confidence: 99%